Foreign experience in managing physical culture and sports on the example of China - N. A. Ushakova (Путеводитель предпринимателя)
This article presents an analysis of the management of physical culture and sports in China. The attention is focused on the key aspects of management and development of children and youth, mass sports, as well as Olympic sports. The aspects of preparation for the upcoming Winter Olympic Games–2022 in the PRC are considered. The final part of the manuscript provides recommendations of a recommendatory nature on borrowing positive aspects from the Chinese experience for their adaptation to Russian reality.